Principles of Game Audio and Sound Design : Sound Design and Audio Implementation for Interactive and Immersive Media - Sinclair, Jean-Luc, ....- (New York : Routledge, 2020)
Principles of Game Audio and Sound Design is a comprehensive introduction to the art of sound for games and interactive media using Unity. This accessible guide encompasses both the conceptual challenges of the artform as well as the technical and creative aspects, such as sound design, spatial audio, scripting, implementation and mixing. Beginning with basic techniques, including linear and interactive sound design, before moving on to advanced techniques, such as procedural audio, Principles of Game Audio and Sound Design is supplemented by a host of digital resources, including a library of ready-to-use, adaptable scripts. This thorough introduction provides the reader with the skills and tools to combat the potential challenges of game audio independently.
Keywords: Game Audio; Game Design; Video Games